2021
DOI: 10.3389/fvets.2021.736996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Reproductive Microbiota of Primiparous Cows During Early Postpartum Periods in the Presence and Absence of Endometritis

Abstract: Endometritis has a major impact on fertility in postpartum dairy cows. Since previous studies showed an association between reproductive microbiota and perinatal disease, we monitored both bovine uterine and vaginal microbiota in primiparous cows to elucidate the effect of early postpartum microbiota on endometritis. Uterine and vaginal samples were collected at time points from pre-calving to 35 days postpartum (DPP), and analyzed by 16S rRNA sequencing, combined with ancillary bacterial culture. A total of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…We observed that OTUs 3 and 5 (classified by BLAST as Porphyromonas ) as well as OTU 9 ( Trueperella ) increased in relative abundance from Precalve to Postcalve in agreement with the literature. Their parent genera increased over this interval as well ( 84 , 85 , 110 , 118 ). As discussed previously, Porphyromonas can colonize and invade ruminant uterine tissues and is associated with a number of reproductive tract diseases.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We observed that OTUs 3 and 5 (classified by BLAST as Porphyromonas ) as well as OTU 9 ( Trueperella ) increased in relative abundance from Precalve to Postcalve in agreement with the literature. Their parent genera increased over this interval as well ( 84 , 85 , 110 , 118 ). As discussed previously, Porphyromonas can colonize and invade ruminant uterine tissues and is associated with a number of reproductive tract diseases.…”
Section: Discussionmentioning
confidence: 89%
“…It is well-established in the literature that parturition induces a significant, discrete shift in microbial community structure and composition in the mammalian reproductive tract ( 76 , 84 , 107–110 ). In particular, Bicalho et al and Kudo et al also observed a trend of decrease in alpha diversity in cattle vaginal microbiota following parturition ( 84 , 110 ). The mammalian reproductive tract alpha diversity is also known to shift longitudinally during pregnancy but prior to parturition, corroborating the additional differences between VT combinations of different timepoints as well as the PCoA plots ( 72 , 111–114 ).…”
Section: Discussionmentioning
confidence: 92%
“…There is limited information about the impact of Bacteroides, Prevotella, or Porphyromonas colonization of the vaginal tract in sheep on reproductive performance. However, all three genera have all been associated with cattle experiencing reproductive maladies such as metritis, endometritis, or vaginitis ( Elad et al, 2004 ; Bicalho et al, 2017 ; Cunha et al, 2018 ; Kudo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the vaginal microbiome can affect the reproductive health of cows [ 26 ]. Some harmful strains of bacteria, such as Streptococcus , E. coli , and P. pyogenea , can affect the uterus and ovaries through infection, leading to inflammation and the development of infection.…”
Section: Discussionmentioning
confidence: 99%